The eclipse of the «liberal argentina» and the republican tradition. Reflections on the public discourses of Agustín Justo, Roberto Ortiz and Marcelo T. de Alvear, 1930-1943 (Estudios Sociales, 2018)
The article studies the crisis of «Liberal Argentina», conventionally associated with the coup d’État of 1930 . For this, the public discourses of three unavoidable figures of Argentine politics between 1930 and 1943 are analyzed, who, in addition, thought themselves, and were seen, as liberals: Agustín Justo, Roberto Ortiz and Marcelo T. de Alvear.
Keywords: Argentine politics; 1930 ’s; Liberalism; Republicanism; Democracy